[(2-Pyridyl)methanol-κ(2) N,O]bis(thiocyanato-κN)manganese(II) - Gao, Qihe (International Union of Crystallography, 2010)
In the title complex, [Mn(NCS)(2)(C(6)H(7)NO)(2)], the Mn(II) atom shows site symmetry 2. The distorted octahedral environment of Mn(II) is defined by two N atoms [Mn—N = 2.217 (4) and 2.132 (5) Å] and one O atom [Mn—O 2.305 (4) Å]. There are intermolecular O—H⋯S hydrogen bonds and intermolecular π–π stacking interactions between adjacent (2-pyridyl)methanolate ligands [centroid–centroid distance = 3.5569 (7) Å], leading to a chain structure running along [100].